2019
DOI: 10.1097/scs.0000000000005352
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Knowledge, Attitude and Behaviour toward Cleft Lips and Cleft palate in Kencana Hospital, Serang, Banten

Abstract: Introduction: Cleft lips (CL) and cleft palate (CP) are common congenital diseases caused by gene mutation in embriology development of the lips and mouth at 4 weeks of gestation. CL and CP can cause several problems such as difficulty in eating, speaking, abnormality in teeth and mouth development and ear iritation. Adequate treatment is needed to improve patients’ quality of life. Material and Method: This cross sectional study take samples purposivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…10 A study carried out by Soeselo et al in Serang, Banten showed that the majority of the respondents (96.2%) had inadequate knowledge about cleft lip and palate. 12 On the other hand, Alnujaim et al showed that 52.5% Saudi pregnant women had a good level of knowledge. 11 The results of the research at Puskesmas Mutiara Asahan were different from one of the previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A study carried out by Soeselo et al in Serang, Banten showed that the majority of the respondents (96.2%) had inadequate knowledge about cleft lip and palate. 12 On the other hand, Alnujaim et al showed that 52.5% Saudi pregnant women had a good level of knowledge. 11 The results of the research at Puskesmas Mutiara Asahan were different from one of the previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…This was assessed using several questions regarding the type of cleft, the cause, and the best time to have surgery done. 12 Cleft lip and palate may have a major impact on facial appearance; eating, speech, and dental conditions; as well as respiratory and digestive functions. The risk factor for cleft lip and palate is a combination of genetic factors and environmental factors that are closely related to the condition of the mother during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Biaya yang diperlukan untuk melakukan operasi palatoplasty bukan hanya biaya pembedahan namun termasuk perawatan pra dan post operasi, serta biaya pemulihan. [23] Kondisi kesehatan anak merupakan faktor utama yang menentukan kebutuhan orang tua untuk mencari pengobatan. Pada penelitian ini yang termasuk salah satu komponen faktor kebutuhan orang tua untuk melakukan operasi pada anaknya yaitu orang tua menganggap penting untuk melakukan operasi agar anak dapat berpartisipasi dengan lebih percaya diri dalam lingkungan sosialnya (kotak no 4).…”
Section: Hj Hf (35th)unclassified